The Nature of Papuan Women Indigenous Entrepreneurship in Informal Agricultural Sector (A Case of Papuan Women Traders in Manokwari and Surrounding Areas of West Papua- Indonesia) - Wambrauw, Ludia T.; Martin, Sandra; Addison, Ramzi (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2019)
West Papua, Indonesia, are engaged in marketing activity in informal agricultural sector. However, the nature of their entrepreneurial activity and the factors that impede and enable these endeavors are not clearly understood. The aim of this research is to gain a better understanding of the entrepreneurial marketing activity of these women along with constraints that impede them to identify opportunities for improving their position. A theoretical framework, based on indigenous entrepreneurship literature and knowledge of Papuan context, was designed to guide the research. A qualitative approach was used to investigate three case studies of groups of women in three different areas – a more remote area, a transmigration site, and an urban area. Within-case and cross-case analysis revealed that those Papuan women’s motivation was driven by their immediate family’s needs and their social and cultural obligations. The analysis also indicated that they were proven to be open to innovation. Further, they were outward looking and had market awareness. There was variation between the groups in their engagement with cash economy and the expression of their market awareness. Their implementation of marketing techniques varied, with urban traders employing a wider range of marketing strategies. Women traders from more remote areas and transmigration site depended heavily on their natural resources, whereas the majority of urban traders were more dependent on marketing resources and financial reserves in order to buy produce from other producers. Hence, more remote area and transmigration site traders were self-funded, while urban traders were partly selffunded. Traders from more remote area relied very heavily upon social capital in conducting their production and marketing activities, whereas traders in the other groups were less reliant on social capital. Traders from more remote area faced greater constraints related to poor road access, high cost transportation, and poor access to physical markets. In addition, all traders had poor access to government support. These insights into the varied nature of indigenous entrepreneurship and the differences in constraints faced by different groups provide policy insights for Papuan government.